Linear and Nonlinear Semiconductor Optical Amplifiers for Next-Generation Optical Networks - Bonk, René (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2013)
In this book, semiconductor optical amplifiers (SOAs) are studied with a view to linear and nonlinear applications in next-generation optical networks. Quantum-dot SOAs can be optimized for linear amplification of signals with different modulation formats and multiplexing techniques. Conversely, bulk SOAs can be easily optimized for operation in the nonlinear regime. However, due to the fast carrier recovery times in QD SOAs we also look into nonlinear applications with these devices.